Al4SiC4 ceramic powder and pressure-free preparation method thereof
By directly dry-mixed and heat treatment at 1800-2000°C, the existing Al4SiC4 ceramic material preparation process and pressurization are solved, and the low-cost and efficient preparation of single-phase Al4SiC4 ceramic powder is achieved, simplifying the process flow and reducing manufacturing costs.
Patent Information
- Application Number
- CN202311383102.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-10-24
- Publication Date
- 2025-04-25
AI Technical Summary
The existing preparation methods of Al4SiC4 ceramic materials have problems such as long heating time, large energy consumption, large particle size, need to grind and mix under toxic solvents, complex process, and need to pressurize, making it difficult to achieve the industrial promotion of single-phase Al4SiC4 ceramic powder.
Aluminum powder, silicon powder, activated carbon powder, aluminum carbide powder, and silicon carbide powder, which are directly dry-mixed or evenly mixed with solvent according to the stoichiometric ratio of Al4SiC4, are heat treated and insulated at 1800-2000°C for 2 to 4 hours to obtain a single-phase Al4SiC4 ceramic powder.
The preparation of single-phase Al4SiC4 ceramic powder with low cost, high efficiency, pressure-free and no grinding is achieved, which simplifies the process flow, reduces manufacturing costs, and is easy to industrial batch preparation and promotion.
Smart Images

Figure CN119873823A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of special ceramic material preparation, and specifically relates to an Al4SiC4 ceramic powder and a pressureless preparation method thereof. Background Art
[0002] Al4SiC4 has high melting point, high chemical stability, high strength, low thermal expansion coefficient, and excellent anti-oxidation and anti-hydration properties. It undergoes surface oxidation under high temperature conditions to form a stable mullite and corundum protective film. It can be used as an additive to improve the oxidation resistance of carbon-containing materials and enable the materials to achieve effective self-repair effects. It is a promising high-temperature structural material and high-performance refractory material. At the same time, due to its superior weight-to-weight strength and high-temperature oxidation resistance, it also has great application potential in the aerospace and automotive industries.
[0003] At present, the methods for synthesizing Al4SiC4 mainly include: solid phase reaction sintering, hot pressing sintering, high temperature self-propagating method, infiltration method, mechanical alloying method, etc., among which the most commonly used method is solid phase reaction sintering. K Itatani et al. grind high-purity aluminum powder, silicon powder and activated carbon powder under n-hexane conditions according to the stoichiometric ratio of Al4SiC4, heated to 1600℃ in Ar atmosphere and kept warm for 10 hours to obtain Al4SiC4 powder, which has problems such as long heating time, high energy consumption and large particle size, and needs to be ground and mixed in toxic solvents for preparation. Koji Inoue et al. mixed aluminum powder, silicon powder and carbon powder with acetone, ball-milled for 24 hours, dried and pressed under 80MPa pressure, cold isostatically pressed under 100MPa pressure, and kept at 1700℃ for 4 hours to obtain Al4SiC4 block. The Al4SiC4 ceramic powder was prepared by mechanical processing and grinding, which had the problems of complex preparation process, pressurization, high equipment requirements, etc., and high-purity aluminum powder and silicon powder had high chemical activity and were easy to oxidize to produce oxide impurity layer covering the powder surface, so that the powder preparation process must be preformed by pressure, hot pressing and sintering to destroy the oxide impurity layer and promote the high-temperature mass transfer reaction of the powder, so as to obtain Al4SiC4 product. Therefore, these conventional preparation methods are generally unable to promote the industrialization of single-phase Al4SiC4 ceramic powder. Summary of the invention
[0004] In view of the above technical problems, the object of the present invention is to provide a single-phase Al4SiC4 ceramic powder and a preparation method thereof which is low-cost, high-efficiency, pressure-free, does not require grinding or pulverization, and is easy to prepare in industrial batches.
[0005] In a first aspect, the present invention provides a method for preparing Al4SiC4 ceramic powder, the preparation method comprising: weighing aluminum powder, silicon powder, activated carbon powder or aluminum carbide powder, silicon carbide powder as raw materials according to the stoichiometric ratio of Al4SiC4, directly dry-mixing them evenly or mixing them evenly with a solvent and then drying to obtain a mixed powder; then performing heat treatment to obtain a single-phase Al4SiC4 ceramic powder.
[0006] Preferably, the aluminum powder has a particle size of 100-200 meshes and a purity of ≥99.0%; the silicon powder has a particle size of 1-3 μm and a purity of ≥99.9%; the activated carbon powder has a particle size of 1-100 nm, preferably 20 nm, and a purity of ≥99.9%.
[0007] Preferably, the particle size of the aluminum carbide powder is 1-3 μm, and the purity is ≥99.9%; the particle size of the silicon carbide powder is 0.5-0.7 μm, and the purity is ≥99.0%.
[0008] Preferably, the solvent is at least one of anhydrous ethanol, acetone or n-hexane, preferably anhydrous ethanol.
[0009] Preferably, the drying temperature is ≤50°C and the drying time is 1 to 5 hours.
[0010] Preferably, the heat treatment process is: heating to 1800-2000° C. at a rate of 5-10° C. / min in an inert gas and keeping the temperature for 2-4 hours.
[0011] Preferably, the inert gas of the heat treatment process is argon; the heat treatment pressure is 0 to 0.06 MPa, preferably 0.01 to 0.04 MPa.
[0012] In a second aspect, the present invention provides an Al4SiC4 ceramic powder obtained according to the above preparation method, wherein the Al4SiC4 ceramic powder is a single-phase powder with a particle size of 0.5 to 200 μm, preferably 1 to 20 μm, and a purity of ≥99.0%.
[0013] Beneficial Effects The present invention obtains single-phase Al4SiC4 ceramic powder with a particle size of 0.5 to 200 μm by simply mixing aluminum powder, silicon powder, activated carbon powder or aluminum carbide powder and silicon carbide powder which are chemically stable, easy to store and safer, and heat treating them at 1800 to 2000° C. for 2 to 4 hours. Compared with the traditional preparation method, the preparation route provided by the present invention has a simpler process, does not require preforming and subsequent mechanical crushing, realizes pressure-free and short-time preparation, reduces the requirements for equipment and manufacturing costs, and is easy to realize batch preparation and industrial promotion of single-phase Al4SiC4 ceramic powder. BRIEF DESCRIPTION OF THE DRAWINGS
[0014] Figure 1 This is an X-ray diffraction pattern of the Al4SiC4 ceramic powder prepared in Example 1 of the present invention; Figure 2 This is a SEM image of the Al4SiC4 ceramic powder prepared in Example 1 of the present invention; Figure 3 This is the EDS image of the Al4SiC4 ceramic powder prepared in Example 1 of the present invention. DETAILED DESCRIPTION
[0015] The present invention is further described by way of embodiments. It should be understood that the following embodiments are only used to illustrate the present invention, rather than to limit the present invention.
[0016] The following is an exemplary description of the preparation method of the Al4SiC4 ceramic powder provided by the present invention. The preparation method may include the following steps: weighing aluminum powder, silicon powder, activated carbon powder or aluminum carbide powder or silicon carbide powder with stable chemical properties, easy storage and better safety as raw materials according to the stoichiometric ratio of Al4SiC4, directly dry-mixing or mixing with a solvent and then drying to obtain a mixed powder; and then performing heat treatment to obtain a single-phase Al4SiC4 ceramic powder.
[0017] In some embodiments, the aluminum powder may have a particle size of 100-200 meshes with a purity of ≥99.0%; the silicon powder may have a particle size of 1-3 μm with a purity of ≥99.9%; the activated carbon powder may have a particle size of 1-100 nm, preferably 20 nm, with a purity of ≥99.9%.
[0018] In some embodiments, the particle size of the aluminum carbide powder may be 1 to 3 μm, and the purity may be ≥ 99.9%; the particle size of the silicon carbide powder may be 0.5 to 0.7 μm, and the purity may be ≥ 99.0%.
[0019] The raw material cost of the above particle size and purity range is more advantageous. Within this particle size range, it is conducive to the production of micron-level powders with uniform size. The finer particle size and higher purity are conducive to reducing the heating time required for powder synthesis under pressureless sintering conditions, ensuring the purity of Al4SiC4 ceramic powders.
[0020] The molar content ratio of the raw material powders may be aluminum powder: silicon powder: carbon powder = 4:1:4, or aluminum carbide powder: silicon carbide powder = 1:1.
[0021] In some embodiments, the solvent may be at least one of anhydrous ethanol, acetone or n-hexane, preferably anhydrous ethanol having good safety.
[0022] In some embodiments, the drying temperature may be ≤50° C., and the drying time may be 1 to 5 hours.
[0023] In some embodiments, the heat treatment process may be: wrapping the mixed powder with graphite paper and placing it in a graphite crucible, then heating it to 1800-2000° C. at a rate of 5-10° C. / min in an inert gas, and keeping it warm for 2-4 hours.
[0024] By increasing the heat treatment temperature to 1800-2000°C, the oxide impurities on the surface of high-purity aluminum powder and silicon powder can be melted, the impurity layer structure can be destroyed, and the impurity layer and activated carbon can be promoted to undergo a rapid carbon thermal reduction reaction to remove oxide impurities, thereby reducing the heat treatment time and obtaining Al4SiC4 ceramic powder by pressureless sintering. In addition, the aluminum carbide powder and silicon carbide powder raw materials used in the present invention are chemically stable and will not generate oxide impurities during long-term storage. At 1800-2000°C, the binary raw material powders can quickly transfer mass to generate Al4SiC4 ceramic powder. Compared with the preparation route of the ternary raw materials of aluminum powder, silicon powder and activated carbon powder, the reaction is simpler and easier to carry out.
[0025] The melting point of Al4SiC4 is 2037°C. If the heat treatment temperature exceeds the melting point, the powder will melt and eventually form a block, and Al4SiC4 ceramic powder cannot be directly obtained; if the heat treatment temperature is lower than 1800°C, the mass transfer process is slow under pressureless conditions, which makes the heat treatment time longer and the preparation process inefficient, which is not conducive to industrial promotion; if the holding time is too short, the mass transfer process is not sufficient, and the Al4SiC4 ceramic powder finally obtained contains impurity phases; if the holding time is too long, the grains grow, and the Al4SiC4 powder has a large particle size.
[0026] Preferably, the inert gas of the heat treatment process is argon; the heat treatment pressure is 0 to 0.06 MPa, preferably 0.01 to 0.04 MPa.
[0027] The present invention has simple process, low cost, high efficiency, no pressure, no need for grinding and crushing, and is easy to realize the pressureless industrial batch preparation of single-phase Al4SiC4 ceramic powder. The Al4SiC4 ceramic powder obtained by the preparation method provided by the present invention is a single-phase powder with a particle size of 0.5 to 200 μm, preferably 1 to 20 μm, and a purity of ≥99.0%, which is of great significance for engineering applications such as the preparation of precision parts.
[0028] The following examples are further listed to illustrate the present invention in detail. It should also be understood that the following examples are only used to further illustrate the present invention and cannot be understood as limiting the scope of protection of the present invention. Some non-essential improvements and adjustments made by those skilled in the art based on the above content of the present invention belong to the scope of protection of the present invention. The specific process parameters and the like in the following examples are only examples in a suitable range, that is, those skilled in the art can make a selection within a suitable range through the description herein, and are not limited to the specific values exemplified below.
[0029] Example 1
[0030] The preparation method of Al4SiC4 ceramic powder provided in this embodiment comprises the following steps: According to the stoichiometric ratio of Al4SiC4, 64.75g of aluminum powder (2.4mol, powder particle size 100-200 mesh, purity ≥99.0%), 16.84g of silicon powder (0.6mol, powder particle size 1-3μm, purity ≥99.9%), and 28.82g of activated carbon powder (2.4mol, powder particle size 20nm, purity ≥99.9%) were weighed respectively, and then the raw material powders were directly stirred and dry mixed in a beaker to obtain a mixed powder. The mixed powder was heat treated in a high-temperature sintering furnace. In an inert gas argon atmosphere (the pressure in the furnace was maintained in the range of 0.01 to 0.04 MPa), it was heated to 1800°C at a heating rate of 10°C / min, kept warm for 3 hours, and cooled to room temperature on its own to obtain a single-phase Al4SiC4 ceramic powder.
[0031] Figure 1 This is an X-ray diffraction diagram of the Al4SiC4 ceramic powder prepared in Example 1 of the present invention. It can be seen from the figure that the Al4SiC4 ceramic powder prepared in Example 1 is single-phase Al4SiC4.
[0032] Figure 2 This is a SEM image of the Al4SiC4 ceramic powder prepared in Example 1 of the present invention. It can be seen from the figure that the particle size of the Al4SiC4 ceramic powder prepared in Example 1 is 5 to 15 μm.
[0033] Figure 3 This is the EDS image of the Al4SiC4 ceramic powder prepared in Example 1 of the present invention. It can be seen from the image that the Al element, Si element and C element are evenly distributed without aggregation.
[0034] Example 2
[0035] The preparation method of this embodiment refers to that of Embodiment 1, with the main difference being that each raw material powder is placed in a mortar and anhydrous ethanol is added to grind and mix uniformly, and then placed in an oven to dry at 50° C. for 5 hours to obtain a mixed powder.
[0036] X-ray diffraction analysis, SEM micromorphology analysis, and EDS element analysis were performed on the Al4SiC4 ceramic powder prepared in Example 2 of the present invention, indicating that the prepared powder was single-phase Al4SiC4 with a particle size of 5 to 10 μm, and the Al, Si and C elements were evenly distributed without aggregation.
[0037] Example 3
[0038] The preparation method of this embodiment refers to that of Embodiment 1, with the main differences being: (1) according to the stoichiometric ratio of Al4SiC4, 21.58 g of aluminum powder (0.8 mol, powder particle size of 100-200 mesh, purity ≥99.0%), 5.62 g of silicon powder (0.2 mol, particle size of 1-3 μm, purity ≥99.9%), and 9.61 g of activated carbon powder (0.8 mol, powder particle size of 20 nm, purity ≥99.9%) were weighed respectively; and (2) the heat treatment holding time was 2 hours.
[0039] Example 4
[0040] The preparation method of this embodiment refers to that of Embodiment 1, with the main differences being: (1) according to the stoichiometric ratio of Al4SiC4, 21.58 g of aluminum powder (0.8 mol, powder particle size of 100-200 mesh, purity ≥99.0%), 5.62 g of silicon powder (0.2 mol, particle size of 1-3 μm, purity ≥99.9%), and 9.61 g of activated carbon powder (0.8 mol, powder particle size of 20 nm, purity ≥99.9%) were weighed respectively; and (2) the heat treatment holding time was 4 hours.
[0041] Example 5
[0042] The preparation method of this embodiment refers to that of Embodiment 1, with the main differences being: (1) according to the stoichiometric ratio of Al4SiC4, 21.58 g of aluminum powder (0.8 mol, powder particle size of 100-200 mesh, purity ≥99.0%), 5.62 g of silicon powder (0.2 mol, particle size of 1-3 μm, purity ≥99.9%), and 9.61 g of activated carbon powder (0.8 mol, powder particle size of 20 nm, purity ≥99.9%) were weighed respectively; and (2) the heating rate during heat treatment was 5°C / min.
[0043] Example 6
[0044] The preparation method of this embodiment refers to that of Embodiment 1, with the main differences being: (1) according to the stoichiometric ratio of Al4SiC4, 28.79 g of Al4C3 powder (0.2 mol, particle size 1-3 μm, purity ≥99.9%) and 8.02 g of SiC powder (0.2 mol, particle size 0.5-0.7 μm, purity ≥99.0%) were weighed respectively, and then the raw material powders were placed in a mortar and anhydrous ethanol was added to grind and mix them evenly, and then placed in an oven to dry at 50°C for 5 hours to obtain a mixed powder; (2) the heating rate during the heat treatment was 5°C / min.
[0045] X-ray diffraction analysis and SEM micromorphology analysis of the Al4SiC4 ceramic powder prepared in Example 6 of the present invention showed that the prepared powder was single-phase Al4SiC4 with a particle size of 5 to 10 μm.
[0046] Comparative Example 1
[0047] The preparation method of this comparative example refers to that of Example 1, with the main differences being: (1) according to the stoichiometric ratio of Al4SiC4, 21.58 g of aluminum powder (0.8 mol, powder particle size of 100-200 mesh, purity ≥99.0%), 5.62 g of silicon powder (0.2 mol, particle size of 1-3 μm, purity ≥99.9%), and 9.61 g of activated carbon powder (0.8 mol, powder particle size of 20 nm, purity ≥99.9%) were weighed respectively; and (2) the heat treatment holding time was 1 hour.
[0048] In the Al4SiC4 ceramic powder prepared in Comparative Example 1 of the present invention, there is activated carbon that has not been completely reacted.
[0049] Comparative Example 2
[0050] The preparation method of this comparative example refers to that of Example 1, with the main differences being: (1) according to the stoichiometric ratio of Al4SiC4, 21.58 g of aluminum powder (0.8 mol, powder particle size of 100-200 mesh, purity ≥99.0%), 5.62 g of silicon powder (0.2 mol, particle size of 1-3 μm, purity ≥99.9%), and 9.61 g of activated carbon powder (0.8 mol, powder particle size of 20 nm, purity ≥99.9%) were weighed respectively; and (2) the heat treatment holding time was 5 hours.
[0051] The Al4SiC4 ceramic powder prepared in Comparative Example 2 of the present invention contains blocky solids and has severe grain growth.
[0052] Although the content of the present invention has been described in detail through the above preferred embodiments, it should be appreciated that the above description should not be considered as a limitation of the present invention. After reading the above content, it will be apparent to those skilled in the art that various modifications and substitutions of the present invention will occur. Therefore, the protection scope of the present invention should be limited by the appended claims.
Claims
1. A method for preparing Al4SiC4 ceramic powder, characterized in that: The preparation method comprises: weighing aluminum powder, silicon powder, activated carbon powder or aluminum carbide powder, silicon carbide powder as raw materials according to the stoichiometric ratio of Al4SiC4, directly dry-mixing them evenly or mixing them evenly with a solvent and then drying them to obtain a mixed powder; and then performing heat treatment to obtain a single-phase Al4SiC4 ceramic powder.
2. The preparation method according to claim 1, characterized in that: The particle size of the aluminum powder is 100-200 meshes, and the purity is ≥99.0%; the particle size of the silicon powder is 1-3 μm, and the purity is ≥99.9%; the particle size of the activated carbon powder is 1-100 nm, preferably 20 nm, and the purity is ≥99.9%.
3. The preparation method according to claim 1 or 2, characterized in that: The particle size of the aluminum carbide powder is 1-3 μm, and the purity is ≥99.9%; the particle size of the silicon carbide powder is 0.5-0.7 μm, and the purity is ≥99.0%.
4. The preparation method according to any one of claims 1 to 3, characterized in that The solvent is at least one of anhydrous ethanol, acetone or n-hexane, preferably anhydrous ethanol.
5. The preparation method according to any one of claims 1 to 4, characterized in that: The drying temperature is ≤50°C and the drying time is 1 to 5 hours.
6. The preparation method according to any one of claims 1 to 5, characterized in that: The heat treatment process is: heating to 1800-2000° C. at a rate of 5-10° C. / min in an inert gas and keeping the temperature for 2-4 hours.
7. The preparation method according to any one of claims 1 to 6, characterized in that: The inert gas in the heat treatment process is argon; the heat treatment pressure is 0 to 0.06 MPa, preferably 0.01 to 0.04 MPa.
8. An Al4SiC4 ceramic powder obtained by the preparation method according to any one of claims 1 to 7, characterized in that: The Al4SiC4 ceramic powder is a single-phase powder with a particle size of 0.5 to 200 μm, preferably 1 to 20 μm, and a purity of ≥99.0%.